1997
DOI: 10.1104/pp.113.1.243
|View full text |Cite
|
Sign up to set email alerts
|

Heat Denaturation Profiles of Ribulose-1,5-Bisphosphate Carboxylase/Oxygenase (Rubisco) and Rubisco Activase and the Inability of Rubisco Activase to Restore Activity of Heat-Denatured Rubisco

Abstract: , lllinois 61 801 (A.R.P.)We compared the heat-denaturation profiles of ribulose-l,5-bisphosphate carboxylase/oxygenase (Rubisco) and Rubisco activase and further examined the ability of Rubisco activase to restore the activity of heat-denatured Rubisco originally reported (E. Sánchez de jiménez, 1. Medrano, and E. Martínez-Barajas [1995] Biochemistry 34: 2826-2831). Rubisco was heat-treated in both the carbamylated and uncarbamylated forms and in the presence and absence of 10 mM dithiothreitol (DTT). Both… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
47
0

Year Published

1997
1997
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(49 citation statements)
references
References 19 publications
2
47
0
Order By: Relevance
“…Previous studies have shown that purified leaf and recombinant activase are extremely heat-labile if incubated in the absence of ATP (Robinson and Portis, 1989;Holbrook et al, 1991;Eckardt and Portis, 1997). Our results corroborated these findings, because we observed inactivation of both forms upon exposure to relatively moderate temperatures (i.e.…”
Section: Discussionsupporting
confidence: 82%
“…Previous studies have shown that purified leaf and recombinant activase are extremely heat-labile if incubated in the absence of ATP (Robinson and Portis, 1989;Holbrook et al, 1991;Eckardt and Portis, 1997). Our results corroborated these findings, because we observed inactivation of both forms upon exposure to relatively moderate temperatures (i.e.…”
Section: Discussionsupporting
confidence: 82%
“…Thus, our results seem to indicate that the accumulation of GB in vivo leads to increased thermotolerance of Rubisco activase. This function of GB is of significance for increasing tolerance of plants to high temperatures since Rubisco activase has been shown to be particularly sensitive to inactivation by high temperatures (Crafts-Brandner et al, 1997;Eckhardt and Portis, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…Heat stress primarily affects thermolabile components, especially photosystem II (PSII) [1] [2] [5]- [7] and Rubisco activase in the Calvin cycle [8]- [10]. Physiological and photosynthetic functions could thus be significantly impaired by elevated heat stress.…”
Section: Introductionmentioning
confidence: 99%